Can Technology Abate the Experience of Social Isolation for Those Affected by Dementia? - Faieta, Julie; Faieta, Lily; Leblond, Jean; Routhier, François; Best, Krista (Frontiers in Aging Neuroscience, 2022)
Background. The widespread social isolation measures recently utilized to mitigate the spread of COVID-19 to older adults may have exuded unexpected consequences. Social isolation among older adults is a risk factor for poor health outcomes. Innovative solutions to balancing public safety and health maintenance for those with dementia and their caregivers are needed. Methods. A sample of N=82 dementia caregivers participated in a web-based survey to investigate their perceptions on 1) changes in personal mental health due to isolation from their loved one, and 2) the perceived need for use of smart mobile device app use in these situations. Results. The majority of our sample (87%) reported experiencing negative mental health outcomes beyond those experienced in typical situations. Furthermore, over 70% of caregivers were concerned with the care their loved on received during social isolation. Finally, 67% reported perceived need to use SMD apps in these times of social isolation. Conclusions. Our findings provide preliminary insight into troubling consequences occurring when individuals with dementia are socially isolated from their caregivers. An inverse relationship between SMD app use and poor mental health points to the potential for communication technology to lessen the negative impacts of social isolation, when it becomes necessary to public safety.